Simultaneous evaluation of bioactivity and settleability of activated sludge using fractal dimension as an intermediate variable. (1st July 2020) - Li, Zhi-Hua; Guo, Yao; Hang, Zhen-Yu; Zhang, Tian-Yu; Yu, Han-Qing
Abstract: Bioactivity and settleability of activated sludge are essential for the operation of activated sludge systems in wastewater treatment. In this work, the fractal dimension of sludge image is proposed as a tool to evaluate these two factors. The specific endogenous respiration rate (SOURe ) and the specific quasi-endogenous respiration rate (SOURq ) are found to be more dependent on the 3D structure of sludge than the specific total respiration rate (SOURt ). The relationship between the fractal structure and bioactivity suggests that the bioactivity governs the acceptable upper bound of the fractal dimension (Df ), as at its theoretical maximum of 2.0, the non-porous compact flocs are predominant. The settleability or the biomass concentration determines the acceptable lower bound of Df, as at its theoretical minimum of 1.0, the free-swimming microbes are predominant. Our data reveal that the activated sludge has an acceptable fractal dimension Df in a range of 1.07–1.68. In practice, the fractal dimension should be controlled at a reasonable value as there is a trade-off between the bioactivity and physical structure to achieve better performance. A decrease or increase in the fractal dimension can serve as a signal for the change of the operational status, and this is further elucidated from the perspective of settling tanks using state point analysis. Compared with respirogram measurement, measuring fractal dimension is a complex process and its online implementation is challenging. Also, the measured value varies with the methods used. In addition, the difference in their theoretical values depends on the homogeneity of the sludge structure. Since the fractal dimension Df reflects both bioactivity and settleability of the sludge but is difficult to measure, in this work a relationship between Df and the easily measurable respirogram is established, and a method using the respirogram as a proxy of Df is proposed to control the bioactivity and settleability simultaneously. This respiration-based method is able to simultaneously control aeration and settling tanks, and could serve as an efficient tool for the management of wastewater treatment plants. Graphical abstract: Image 1 Highlights: Bioactivity governs the acceptable upper bound of fractal dimension. Settleability determines the acceptable lower bound of fractal dimension. A desired fractal dimension has a trade-off between bioactivity and settleability. Fractal dimension can serve as a signal for the change of plant operational status.